Diaphragmatic Hernia as a Prenatal Feature of Glycosylphosphatidylinositol Biosynthesis Defects and the Overlap With Fryns Syndrome – Literature Review - Kosinski, Przemyslaw (Front Genet, 2021)
Fryns syndrome is an autosomal recessive multiple congenital anomaly syndrome, with diaphragmatic defects and secondary lung hypoplasia as cardinal features. Despite it was reported first in 1979, its exact etiology has not been established to date. With this review, we would like to draw attention to the prenatal presentation of multiple congenital anomalies syndromes, resulting from defects in the synthesis of glycosylphosphatidylinositol anchors, to be considered in a prenatal assessment of fetuses with DH and Fryns-like phenotype.